The cost of cure: Examining objective and subjective financial toxicity in head and neck cancer survivors. Issue 10 (8th July 2021) - Baddour, Khalil; Fadel, Mark; Zhao, Meng; Corcoran, Michael; Owoc, Maryanna S.; Thomas, Teresa H.; Sabik, Lindsay M.; Nilsen, Marci L.; Ferris, Robert L.; Mady, Leila J.
Abstract: Background: Little is documented regarding objective financial metrics and their impact on subjective financial toxicity in head and neck cancer (HNC) survivors. Methods: In a cross‐sectional analysis, 71 survivors with available claims data for HNC‐specific out‐of‐pocket expenses (OOPE) completed a survey including patient‐reported, subjective financial toxicity outcome tools: the Comprehensive Score for financial Toxicity (COST) and the Financial Distress Questionnaire (FDQ). Results: Worse COST scores were significantly associated with lower earnings at survey administration (coefficient = 3.79; 95% CI 2.63–4.95; p  < 0.001); loss of earnings after diagnosis (coefficient = 6.03; 95% CI 0.53–11.52; p  = 0.032); and greater annual OOPE as a proportion of earnings [log10(Annual OOPE:Earnings at survey): coefficient = −5.66; 95% CI −10.28 to −1.04; p  = 0.017]. Similar results were found with FDQ. Conclusion: Financial toxicity is associated with particular socioeconomic characteristics which, if understood, would assist the development of pre‐treatment screening tools to detect at‐risk individuals and intervene early in the HNC cancer survivorship trajectory.